Frequently asked questions : trade in services, Barbados - George, Carol (Ministry of Foreign Affairs and Foreign Trade. Foreign Trade Division St. MichaelBB, 2007)
Provides brief answers to some of the more frequently asked questions on the WTO Agreement on Trade in Services. Focuses on the national and international rules affecting cross-border economic transactions, particularly sales of services.